Aborsi dalam Perspektif Hukum Islam - Mardani, Mardani (UI Scholars Hub, 2021)
Islam is a religion that has its own law, which is known as an Islamic Law, which has five main aims. And, one of the five main aims is to save and protect the soul of human from any threats, which means to protect the existence of human beings’ lige and the Moslem community. To concrete it, Islam stated the Law for abortion, Qisas and Diyat. This is a sign of the Islamic Law fort to protect the human life. Considering the complicated problem of baortion thus in this article will be explained the views of Islamic Law on abortion